Cross-border effectiveness of judicial decisions assisted by artificial intelligence in the European Judicial Area - López Rodríguez, Ana Mercedes (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The increasing integration of algorithmic systems into judicial processes, as tools to assistdecision-making, has raised questions about their compatibility with fundamental principles of PrivateInternational Law, such as transparency, due process, and international public policy. The presentarticle analyzes key issues in this context, including the need to harmonize international standards onalgorithmic transparency and technical certification, the limits of public policy in relation to automateddecisions, and the transformation of the normative framework to ensure legal certainty in a globalizedenvironment. Finally, the article proposes recommendations for developing a regulatory framework thatintegrates technological innovation into justice systems without compromising essential principles ofPIL. This analysis aims to contribute to the debate on how to balance technological efficiency with legalsafeguards in the cross-border recognition of AI-assisted judicial decisions
Keywords: Artificial Intelligence (AI); Recognition and Enforcement of Foreign Judicial Decisions; Algorithmic Transparency; Technical Certification; International Public Policy; Algorithmic Justice; Automated Decisions; Legal Certainty; International Judicial Cooperation